Enzyme mediated incorporation of zirconium-89 or copper-64 into a fragment antibody for same day imaging of epidermal growth factor receptor. Issue 26 (16th June 2021) - Rudd, Stacey E.; Van Zuylekom, Jessica K.; Raicevic, Anna; Pearce, Lesley A.; Cullinane, Carleen; Williams, Charlotte C.; Adams, Timothy E.; Hicks, Rodney J.; Donnelly, Paul S.
Abstract : Enzymatic bioconjugation to introduce positron-emitting radionuclides ( 89 Zr, 64 Cu) into an anti-EGFR antibody fragment allows same day imaging with positron emission tomography. Abstract : Identification of tumors which over-express Epidermal Growth Factor Receptor (EGFR) is important in selecting patients for anti-EGFR therapies. Enzymatic bioconjugation was used to introduce positron-emitting radionuclides ( 89 Zr, 64 Cu) into an anti-EGFR antibody fragment for Positron Emission Tomography (PET) imaging the same day as injection. A monovalent antibody fragment with high affinity for EGFR was engineered to include a sequence that is recognized by the transpeptidase sortase A. Two different metal chelators, one for 89 Zr IV and one for 64 Cu II, were modified with a N-terminal glycine to enable them to act as substrates in sortase A mediated bioconjugation to the antibody fragment. Both fragments provided high-quality PET images of EGFR positive tumors in a mouse model at 3 hours post-injection, a significant advantage when compared to radiolabeled full antibodies that require several days between injection of the tracer and imaging. The use of enzymatic bioconjugation gives reproducible homogeneous products with the metal complexes selectively installed on the C-terminus of the antibody potentially simplifying regulatory approval.